2018
DOI: 10.1103/physrevlett.120.055101
|View full text |Cite
|
Sign up to set email alerts
|

Spacecraft Observations of Oblique Electron Beams Breaking the Frozen-In Law During Asymmetric Reconnection

Abstract: Fully kinetic simulations of asymmetric magnetic reconnection reveal the presence of magnetic-field-aligned beams of electrons flowing toward the topological magnetic x line. Within the ∼6d_{e} electron-diffusion region, the beams become oblique to the local magnetic field, providing a unique signature of the electron-diffusion region where the electron frozen-in law is broken. The numerical predictions are confirmed by in situ Magnetospheric Multiscale spacecraft observations during asymmetric reconnection at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
5
16
0
Order By: Relevance
“…In and near EDRs observed by MMS at the dayside magnetopause, crescent-shaped agyrotropic electron distributions perpendicular to the magnetic field have been observed at the magnetospheric side of the EDR (e.g., Chen et al, 2016;Webster et al, 2018) as a result of electron meandering motion in the thin magnetic field reversal (Lapenta et al, 2017), which are consistent with particle simulations (e.g., Bessho et al, 2017;Hesse et al, 2014;Shay et al, 2016). These electron crescents can become oblique due to the presence of the parallel electric field or the electron inertia if the magnetic field lines rotate rapidly (Egedal et al, 2018). Electron crescents were also found at the magnetosheath side of the Hall region during an MMS near-EDR crossing owing to electron finite gyroradius effect.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…In and near EDRs observed by MMS at the dayside magnetopause, crescent-shaped agyrotropic electron distributions perpendicular to the magnetic field have been observed at the magnetospheric side of the EDR (e.g., Chen et al, 2016;Webster et al, 2018) as a result of electron meandering motion in the thin magnetic field reversal (Lapenta et al, 2017), which are consistent with particle simulations (e.g., Bessho et al, 2017;Hesse et al, 2014;Shay et al, 2016). These electron crescents can become oblique due to the presence of the parallel electric field or the electron inertia if the magnetic field lines rotate rapidly (Egedal et al, 2018). Electron crescents were also found at the magnetosheath side of the Hall region during an MMS near-EDR crossing owing to electron finite gyroradius effect.…”
Section: Introductionsupporting
confidence: 75%
“…(5) The agyrotropic electrons here are mainly distributed around the perpendicular plane. These agyrotropic distributions are explained by electron gyromotion at thin electron-scale boundaries and could be different from the EDR cases, where the transition from perpendicular crescents into parallel crescents has been observed owing to the parallel electric field and/or the electron inertia Egedal et al, 2018). Based on the observations above, we conclude that reconnection here is not active, and a similar electron-scale current sheet without bursty reconnection signatures has been reported in the magnetotail (Wang et al, 2018).…”
Section: Discussion and Summarymentioning
confidence: 55%
See 1 more Smart Citation
“…NASA's Magnetospheric Multiscale (MMS) mission [14] was specially designed to characterize the fine scale structure of magnetic reconnection in Earth's magnetosphere and has successfully recorded reconnection events for a range of environments in the magnetosphere [15]. These include asymmetric reconnection events in the dayside magnetopause [16], where electron beams oblique to the magnetic lines of force break the frozen-in law [17]. However, so far, no direct observations have been reported on how the electron frozen-in law is broken during symmetric reconnection in the magnetotail.…”
Section: Please Provide Feedbackmentioning
confidence: 99%
“…The interpretation of measurements of reconnection regions relies heavily on comparing data to the signatures derived from kinetic numerical models (e.g., [7][8][9][10][11][12][13][14][15][16]). In recent work, we found that the details of the reconnection region, including both the electron diffusion region and the reconnection exhaust out to ion scales, depend sensitively on the parameters of the numerical simulations [17].…”
Section: Introductionmentioning
confidence: 99%